The Impact of Social Identities and Public Goods on Electoral Violence in Africa: Lessons for a Better Election Administration (Global Journal of Human-Social Science, 2018)
The long period of colonial rule in Africa came to an end in the four decades between 1950 to 1990 and revolutionized the political landscape of the continent. Apart from the springing up of independent states in the continent these four decades witnessed the resurgence of nationalism, not against colonial rule but within the new states as ethnic and religious enclaves which were isolated during the colonial period saw the new state as one in which its objective within it is to gain political hegemony and control the resources for the benefit of its own enclave -a situation which has become the primary source of political competition and violence. Armed with this observation, this study examined the linkages between social identities (ethnicity and religious polarization) and public goods (dividend of political office) and electoral violence in these emergent African democracies drawing evidence from Nigeria and Kenya. The methodology adopted in the study is content analysis based on data obtained from the POLITY IV and State Failure Datasets. This data was augmented with information obtained from electoral bodies -the Independent National Electoral Commission and Independent Electoral and Boundary in Nigeria and Kenya respectively and some other secondary sources (books, periodicals etc).
Keywords: ethnicity; religious polarization; election; dividend of political office; electoral violence; democracy